2009
DOI: 10.1080/00071660903261944
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 25-hydroxycholecalciferol and soy isoflavones supplementation on bone mineralisation of quail

Abstract: 1. The effects of 25-hydroxycholecalciferol (25-OH-D(3)) and soy isoflavones supplementation on performance, carcase recovery, bone mineral density, and tibia ash, Ca, P, and serum vitamin D concentrations and alkaline phosphatase activity in the Japanese quail (Coturnix coturnix japonica) exposed to high ambient temperature were evaluated. 2. A total of 270 ten-d-old Japanese quail were randomly assigned to 9 treatment groups, 6 replicates of 5 birds each in a 2 x 3 x 3 factorial arrangement of treatments. Bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 47 publications
(63 reference statements)
1
9
0
Order By: Relevance
“…This result may be attributed to the fact that the activity of cholecalciferol, 25(OH)D 3 , and 1,25(OH) 2 D 3 depend on the biological response of birds (Aburto et al, 1998). Sahin et al (2009) obtained better bone mineralization in laying quails when 25(OH)D 3 was added to the diet.…”
Section: Effect Of Different Vitamin D Sources and Calcium Levels In mentioning
confidence: 99%
“…This result may be attributed to the fact that the activity of cholecalciferol, 25(OH)D 3 , and 1,25(OH) 2 D 3 depend on the biological response of birds (Aburto et al, 1998). Sahin et al (2009) obtained better bone mineralization in laying quails when 25(OH)D 3 was added to the diet.…”
Section: Effect Of Different Vitamin D Sources and Calcium Levels In mentioning
confidence: 99%
“…Calcium concentration in tibia was determined by an atomic absorption spectrophotometer, and P was determined by the vanadium molybdate colorimetric method. The ash content of tibia was expressed as ash per unit tibial length, and expressed as a percentage of dry weight (28). BMD in tibia was measured using a Qdr-4500w dual energy X-ray bone mineral density detector.…”
Section: Calcium and Phosphorus Depositionmentioning
confidence: 99%
“…A recent study carried out in young healthy Gambian men to asses the effect on serum 25(OH)D after administration of a single dose of calcidiol Recent animal studies have shown that calcidiol is better absorbed in the intestine than cholecalciferol when added to animal feed (i.e., nutrient and/or supplement). This is further underlined by greater effects of calcidiol in reproductive performance, immune protection against infections, and skeletal turnover markers as compared to parental vitamin D3 in vivo in animals [77][78][79]. Recently, calcidiol supplementation in pregnant gilts, in addition to the control diet containing cholecalciferol, has been shown to improve feral skeletal muscle development and myoblast activity, likely improving postnatal muscle growth [80].…”
Section: Clinical Use Of the 25-hydroxylated Compound Calcidiolmentioning
confidence: 92%